Diseño de un sistema de comunicación inalámbrica para pago electrónico de peajes - Bermudez, Giovanni (Tecnura, 1999)
This document presents academics experiences about the design of a wireless communications system at microwave frequencies for applications in electronic toll collection. This work was based in Gallium Arsenium (HgaAsIV - F20) technology of Gec-Marconi Company.